On positional connections of central punctors space - Žiaukienė, S. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:С. П. Жяукене. Связности в пространстве центральных пункторовS. Žiaukienė. Centrinių punktorių erdvės sąryšiai